SYARIAH DAN TASAWUF LOKAL: Studi Tentang Perdebatan Legalitas Wahidiyah - Moh Ulumuddin (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2013)
Even it's not intensively intermediate and classic period, in the reality debate between and syariah of mysticism is still happened in Islam world specially Indonesia. Errant Religious Advices of Ceremony Moslem Scholai Indonesia (MUI) Sub-Province of Tasikmalaya to stream of mysticism Shalawa, Wahidiyah is fact which cannot be denied. Religious advices of MUI assess the teaching of Wahidiyah about Ghauts Hadza al-Zaman is perverting anc misleading. MUI also urge to society practicing Shalawat Wahidiyah tc immediately repented and back to that real correct Islam teaching. Not only, the religious advices institute also recommend to government to prohibit spreading and freezing of teaching or knowledge of Wahidiyah but also close all of activity place. Keyword: mysticism, Shalawat Wahidiyah, Ghauts Hadza al-Zaman